Correlation Between Smoking and Il-1 Level and Arterial Stiffness as Measured By Cavi in the Young Adult Population Without other Cardiovascular Risk Factors. - Galih Prakosa, Ardani; Tjahjono, Cholid Tri; Kurnianingsih, Novi; Sargowo, Djanggan; Anjarwani, Setyasih (Heart Science Journal, 2023)
Background: Recent studies have shown that arterial stiffness is a strong predictor of cardiovascular events and all-cause mortality, with CAVI (Cardio-Ankle Vascular Index) as a non-invasive arterial stiffness testing method indaily practice.Objective: This study was conducted to examine the relationship between smoking -as a risk factor for arterial stiffness- and CAVI values, as well as levels of IL-1β (Interleukin 1β) as a cytokine that plays a role in the pathophysiology of arterial stiffness.Methods: Eighty-four participants, including smokers and non-smokers without other cardiovascular risk factors, were included in the study. Demographic data, medical history, and smoking behavior were taken using a questionnaire, then IL-1β and CAVI levels were examinedResults: The mean level of IL-1β in smoking subjects was significantly higher (15.09 ± 0.48) than in non-smoking subjects (5.53 ± 0.79; p=0.001). CAVI values in smoking subjects were also significantly higher (8.0 ± 0.06) than in non-smoking subjects (6.9 ± 0.02; p=0.001). Further analysis showed a strong positive correlation between smoking and IL-1β levels (r=+0.776; p=0.001) and CAVI values (r=+0.759; p=0.001).Conclusion: This study shows that smoking significantly correlates with IL-1β levels and CAVI values. The greater number of cigarettes used per day and the longer duration of smoking, there was a positive correlation between IL-1β levels and arterial stiffness as measured by CAVI.